The VaR for the risk management of the investment portfolio - Chambi Condori, Pedro Pablo (2019)
Objective: Analyze how the daily profitability, the variance of each of the components of an investment portfolio and the correlation between the portfolio assests have an incidence in the VaR of the investment portfolio. Method: It is a type of quantitative, descriptive, explanatory with a quantitative approach; that have as a based on the quantification of the average value and the VaR of the investment portfolio. The sample selected by convention was conform by 8 titles that listed on the Peruvian Securities Market, of which, was selected 3 equities assets with which formed a portfolio of equity investments, with the daily quoted data from January 2014 to December 2017. Results: The VaR of the portfolio and the average value of the portfolio are obtained by applying the MonteCarlo simulation for a variation scenario of average daily profitability of 10%, it is verified that the volatility of the portfolio has a direct incidence on the VaR and the profitability influence in the VaR directly. Conclusions: Applying the Harry Markowitz diversification theory and the MonteCarlo simulation, the results obtained prove the effect of the variation in profitability and volatility on the VaR value and on the average value of the portfolio.